Antipartyism and Public Opinion toward Presidential Unilateral Actions: The Case of Taiwan in 2017. (3rd October 2019) - Tsai, Tsung-han; Yu, Ching-hsin
Abstract: In this article, we examine how antipartyism influences the public's preferences for the tools of presidential power by focusing on the case of Taiwan, which is a president-parliamentary system. We distinguish two types of antipartyism: general antipartyism and reactive antipartyism. The former refers to the general perception of political parties, whereas the latter involves the functions of parties in modern democracy. According to the analysis results, we find that general antipartyism is positively associated with support for the president's power to unilaterally appoint judges. In contrast, reactive antipartyism leads to less support for executive privilege, unilateral judicial appointments, and the authority to direct agency implementation of policies passed by the legislature.